The effect of osteopathic manipulative treatment on lenght of stay and pain relief in pediatric appendectomy: a pilot non-randomized time-controlled clinical trial - Lo Piccolo, Roberto; Cantagalli, Michele Maria; Ferroni, Tommaso; Fracchiolla, Florinda; Morabito, Antonino (Frontiers in Pediatrics, 2025)
IntroductionAppendicitis is the most frequent non-traumatic surgical emergency in children. While laparoscopic surgery is standard, postoperative recovery often involves pain, delayed bowel function, and reduced mobility. Osteopathic manipulative treatment (OMT) may improve recovery by addressing fascial restrictions and visceral dysfunction. This pilot study investigates OMT's effect on postoperative pain and hospital length of stay in pediatric patients undergoing appendectomy.MethodsThis non-randomized, time-controlled clinical trial was conducted at Meyer Pediatric Hospital (Florence, Italy) with 43 patients aged 5–17 undergoing laparoscopic appendectomy. Participants were divided by appendicitis type (complicated/uncomplicated) and treatment group (OMT vs. control). The OMT group received two standardized sessions within 48 h post-surgery. Primary outcomes included postoperative pain (assessed via Numeric Rating Scale) and hospital stay. Secondary outcomes included bowel function, mobilization, and nausea/vomiting. Data were analyzed using multivariate statistics and t-tests, with p < 0.05 as the significance threshold.ResultsThe OMT group showed a shorter mean hospital stay (4.6 vs. 7 days) and significantly greater reductions in abdominal and shoulder pain compared to controls. In uncomplicated appendicitis, pain reduction reached 3/10 vs. 1.7/10 in controls; in complicated cases, 3.6/10 vs. 1.8/10. Shoulder pain relief was also more pronounced in the OMT groups. Improvements in bowel function, mobilization, and nausea were observed in both groups, with no statistically significant differences.ConclusionsThis pilot study provides preliminary evidence that OMT may enhance postoperative recovery in pediatric appendectomy by reducing pain and potentially shortening hospital stays. Although not statistically significant due to the small sample size, the clinical relevance of these findings supports further investigation through larger, randomized trials.